EXPLAINING IRRATIONALITY - Garcia Zarate, Oscar Augusto (2009)
All current approaches to rationality are funded on the presupposition that an agentacts to maximize his own qualification. But in our daily experiences all of us are facedwith phenomena such as believing in something that we would like to be true or actingagainst what we rhink is best. This paper tries to give an explanation to diftúent waysof being irrational.